The Influence of Leadership and Incentives on Teacher Performance with Motivation as A Moderating Variable at Public Madrasah Aliyah in Pontianak City - Rahmi, Tazkia Lailia; Hartono, Arif (Jurnal Pendidikan Indonesia, 2025)
This study aims to determine how leadership and incentives affect teacher performance with motivation as a moderating variable. The research was conducted using quantitative methods. Data were obtained using a sample of 128 teachers from three State Aliyah Madrasah in Pontianak City. The data were analyzed using linear regression techniques with the help of SPSS statistical software. The results showed that both leadership and incentives had a positive and significant effect on teacher performance mediated by motivation. Partially, leadership and incentives also have a positive and significant effect on both teacher motivation and performance.